Shifting Paradigms for Suppressing Fibrosis in Kidney Transplants: Supplementing Perfusion Solutions With Anti-fibrotic Drugs - van Leeuwen, L. Leonie; Leuvenink, Henri G. D.; Olinga, Peter; Ruigrok, Mitchel J. R. (Frontiers in Medicine, 2022)
Great efforts have been made toward addressing the demand for donor kidneys. One of the most promising approaches is to use kidneys from donation after circulatory death donors. These kidneys, however, suffer from more severe ischemia and reperfusion injury than those obtained via donation after brain death and are thus more prone to develop interstitial fibrosis and tubular atrophy. Even though machine perfusion is increasingly used to reduce ischemia and reperfusion injury, there are no effective treatments available to ameliorate interstitial fibrosis and tubular atrophy, forcing patients to resume dialysis, undergo re-transplantation, or suffer from premature death. Safe and effective anti-fibrotic therapies are therefore greatly desired. We propose a new therapeutic approach in which machine perfusion solutions are supplemented with anti-fibrotic compounds. This allows the use of higher concentrations than those used in humans whilst eliminating side effects in other organs. To the authors' knowledge, no one has reviewed whether such an approach could reduce interstitial fibrosis and tubular atrophy; we therefore set out to explore its merit. In this review, we first provide background information on ischemia and reperfusion injury as well as interstitial fibrosis and tubular atrophy, after which we describe currently available approaches for preserving donor kidneys. We then present an evaluation of selected compounds. To identify promising compounds, we analyzed publications describing the effects of anti-fibrotic molecules in precision-cut kidneys slices, which are viable explants that can be cultured ex vivo for up to a few days whilst retaining functional and structural features. LY2109761, galunisertib, imatinib, nintedanib, and butaprost were shown to exert anti-fibrotic effects in slices within a relatively short timeframe (<48 h) and are therefore considered to be excellent candidates for follow-up ex vivo machine perfusion studies.